Lyrics in Aespa’s “Life’s Too Short” and Olivia Rodrigo’s “Traitor” - Putri Anastasia Silalahi; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study performs a semantic analysis of the song lyrics from "Life’s Too Short" by Aespa and "Traitor" by Olivia Rodrigo, aiming to uncover how words convey deeper meanings and emotions. Employing a descriptive qualitative method and drawing on the semantic frameworks of Adisutrisno (2008) and Chaer (2013), the research investigates the types of meaning—conceptual, connotative, and associative—alongside various forms of figurative language. Data for both songs were collected through literature reviews and online lyric sources. The analysis of Aespa's "Life’s Too Short" primarily identifies conceptual meanings and idioms, highlighting their role in conveying the song's core message. For Olivia Rodrigo's "Traitor," the study reveals a richer tapestry of semantic meanings, including connotative, conceptual, and associative meanings, complemented by the presence of simile, personification, metaphor, and paradox as prominent types of figurative language.